Influence of selenium supplementation on carbohydrate metabolism and oxidative stress in pregnant women with gestational diabetes mellitus - Saifi, Hadjer (J Med Biochem, 2020)
BACKGROUND: In the presence of conflicting advice about the relationship between selenium-type II diabetes-oxidative stress trio, this study aimed to assess the consequences of selenium supplementation on fasting plasma glucose (FPG) level, antioxidant activities of selenodependent and non-selenodependent enzymes, and other markers of oxidative stress studied for the first time during gestational diabetes mellitus (GDM). METHODS: This research was carried out among 180 pregnant Algerian women, 60 of whom were in good health, 60 women with GDM did not take supplements, and 60 women with GDM took selenium orally (50 mg/d) for 12 weeks starting from their second trimester of pregnancy. Blood samples were taken in order to assay FPG level and oxidative stress markers. RESULTS: Selenium supplementation during GDM has demonstrated its hypoglycemic power in the significant decline of FPG level, and its antioxidant properties in the significant reinforcement of antioxidant activities of erythrocyte selenodependent enzymes (glutathione peroxidase and glutathione reductase), the significant increase in erythrocyte catalase and superoxide dismutase activities simultaneously with the highest decrease in erythrocyte and plasma malondialdehyde levels. This decrease was only significant for plasma carbonyl proteins, which was not the case for erythrocyte carbonyl proteins. CONCLUSIONS: The recourse to selenium supplementation by seleno-deficient pregnant women with GDM is beneficial for maternal health. This micronutrient exploits its antioxidant and insulin-mimetic properties in the maintenance of blood glucose homeostasis and the fight against oxidative stress, and consequently, its supplementation delays the occurrence of GDM complications.